1985
DOI: 10.1093/infdis/151.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vancomycin Plus Rifampin in Experimental Aortic-Valve Endocarditis Due to Methicillin-Resistant Staphylococcus aureus: In Vitro-in Vivo Correlations

Abstract: Studies of in vitro and in vivo bactericidal interactions of vancomycin plus rifampin against Staphylococcus aureus have yielded conflicting results. In this study the efficacy of this drug combination in experimental endocarditis due to a methicillin-resistant strain of S. aureus was investigated. Left-sided endocarditis was induced in 84 rabbits by an infecting strain that had been found to be synergistically killed by vancomycin plus rifampin in vitro when tested by the timed-kill curve technique; in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 24 publications
7
59
1
2
Order By: Relevance
“…For example, vancomycin penetration into lung tissue is not sustained, and the same was seen for the meninges and infected bone, whereas rifampin easily penetrates these tissues (61,109,120). The rifampin-vancomycin in vitro interaction appears to range from antagonistic to indifferent, with very few synergistic studies (25,26,112,119,158,218,246,251,258,261). Tuazon et al showed that the rifampin-vancomycin combination had "partial synergism" with only 25% of the MSSA isolates, with the remainder being indifferent, while the nafcillin-rifampin combination had "partial synergism" for 60% of the isolates (246).…”
Section: Staphylococcimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, vancomycin penetration into lung tissue is not sustained, and the same was seen for the meninges and infected bone, whereas rifampin easily penetrates these tissues (61,109,120). The rifampin-vancomycin in vitro interaction appears to range from antagonistic to indifferent, with very few synergistic studies (25,26,112,119,158,218,246,251,258,261). Tuazon et al showed that the rifampin-vancomycin combination had "partial synergism" with only 25% of the MSSA isolates, with the remainder being indifferent, while the nafcillin-rifampin combination had "partial synergism" for 60% of the isolates (246).…”
Section: Staphylococcimentioning
confidence: 99%
“…Outcomes were determined by determinations of valvular bacterial CFU, rates of valvular sterilization, and overall cure. In this well-controlled environment, the combination therapy was significantly better in all of these parameters and prevented rifampin resistance (25) (119,198). Kaatz The described in vivo data for rifampin combination therapy for S. aureus endocarditis have several limitations that affect whether the results could be applied clinically.…”
Section: Staphylococcimentioning
confidence: 99%
“…In view of the fact that results of testing such combinations by various methods do not always reveal concordant interactions, it is not surprising that in vitro data do not always predict in vivo efficacy (15). Interactions between various agents often used in combination for the treatment of staphylococcal infections may be quite complex, including elements of synergism, antagonism, and suppression of resistant subpopulations, and may be method and concentration dependent.…”
Section: Staphylococcimentioning
confidence: 99%
“…Although the bactericidal agent rifampin has excellent antistaphylococcal activity, the emergence of rifampin resistance when used as a single agent has limited its use in this manner (19)(20)(21). This development of rifampin resistance in infections that are difficult to treat (endocarditis and osteomyelitis) has been documented in many papers and supports the requirement that rifampin should not be administered as a single agent (2,4,8,9,13). Studies of the combination of rifampin and other antibacterials have reported mixed results, with several studies reporting antagonism or indifference (2,5,17,18).…”
mentioning
confidence: 94%